A Discourse Analysis of Jakarta Globe in Advertisements - Endah Mitsalina (ETERNAL (English Teaching Journal), 2016)
This study analyzes the idea of the discourse of advertising. The emphasis is on consumer advertising, which is coordinated towards the advancement of some item or service to the public. The study, nonetheless, is not intended to debilitate every one of the parts of this specific discourse, or present a response to every one of the issues it postures. Or maybe, it goes for revealing the essential components of the most unavoidable, persuasive and inescapable discourse of the 21st century; the promoting content. This study provides analyses of advertisement, using different contexts. It covers linguistic context, situational context, and cultural context.